Temple Destruction, Mourning and Curse in Elephantine, with a View to Lamentations - Granerød, Gard (Zeitschrift für die alttestamentliche Wissenschaft, 2020)
The article discusses the lament over the Temple of YHW in Elephantine from three angles: from the perspective of the internal rhetoric or composition of the letter, from the perspective of the world of the Judaeans who wrote the petition, and from the perspective of the world of the intended recipient of the letter. In addition, the article explores how the mention of collective mourning and curse in the petition letter from Elephantine may provide a text of comparison - and context - for the laments over the destruction of the city of Zion and her temple found in the Book of Lamentations.